Temporal Variability of Microparticles Under the Seattle Aquarium, Washington State: Documenting the Global Covid‐19 Pandemic. (22nd September 2021) - Harris, Lyda S.T.; La Beur, Laura; Olsen, Amy Y.; Smith, Angela; Eggers, Lindsey; Pedersen, Emily; Van Brocklin, Jennifer; Brander, Susanne M.; Larson, Shawn
Abstract: Anthropogenic debris including microparticles (<5 mm) are ubiquitous in marine environments. The Salish Sea experiences seasonal fluctuations in precipitation, river discharge, sewage overflow events, and tourism—all variables previously thought to have an impact on microparticle transport and concentrations. Our goals are two‐fold: 1) describe long‐term microparticle contamination data including concentration, type, and size; and 2) determine if seasonal microparticle concentrations are dependent on environmental or tourism variables in Elliott Bay, Salish Sea. We sampled 100 L of seawater at a depth of approximately 9 m at the Seattle Aquarium, Seattle, Washington State, United States, approximately every two weeks from 2019 through 2020 and used an oil extraction protocol to separate microparticles. We found that microparticle concentrations ranged from 0 to 0.64 particles L −1 and fibers were the most common type observed. Microparticle concentrations exhibited a breakpoint on 10 April 2020, where estimated slope and associated microparticle concentration significantly declined. Further, when considering both environmental as well as tourism variables, temporal microparticle concentration was best described by a mixed‐effects model, with tourism as the fixed effect and the person counting microparticles as the random effect. Although monitoring efforts presented set out to identify effects of seasonality and interannual differences in microparticle concentrations, it instead captured an effect of decreased tourism due to the global Covid‐19 pandemic. Long‐term monitoring is critical to establish temporal microparticle concentrations and to help researchers understand if there are certain events, both seasonal and sporadic (e.g., rain events, tourism, or global pandemics), when the marine environment is more at risk from anthropogenic pollution. Environ Toxicol Chem 2022;41:917–930. © 2021 Seattle Aquarium. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.